17β-estradiol regulates the sexually dimorphic expression of BDNF and TrkB proteins in the song system of juvenile zebra finches. - Yu Ping Tang; Juli Wade (PLoS ONE, 2012)
Mature brain derived neurotrophic factor (BDNF) plays critical roles in development of brain structure and function, including neurogenesis, axon growth, cell survival and processes associated with learning. Expression of this peptide is regulated by estradiol (E2). The zebra finch song system is sexually dimorphic - only males sing and the brain regions controlling song are larger and have more cells in males compared to females. Masculinization of this system is partially mediated by E2, and earlier work suggests that BDNF with its high affinity receptor TrkB may also influence this development. The present study evaluated expression of multiple forms of both BDNF and TrkB in the developing song system in juvenile males and females treated with E2 or a vehicle control. Using immunohistochemistry and Western blot analysis, BDNF was detected across the song nuclei of 25-day-old birds. Westerns allowed the pro- and mature forms of BDNF to be individually identified, and proBDNF to be quantified. Several statistically significant effects of sex existed in both the estimated total number of BDNF+ cells and relative concentration of proBDNF, varying across the regions and methodologies. E2 modulated BDNF expression, although the specific nature of the regulation depended on brain region, sex and the technique used. Similarly, TrkB (both truncated and full-length isoforms) was detected by Western blot in the song system of juveniles of both sexes, and expression was regulated by E2. In the context of earlier research on these molecules in the developing song system, this work provides a critical step in describing specific forms of BDNF and TrkB, and how they can be mediated by sex and E2. As individual isoforms of each can have opposing effects on mechanisms, such as cell survival, it will now be important to investigate in depth their specific functions in song system maturation.